Epitope-Specific Suppression of IgG Responses by Passively Administered Specific IgG: Evidence of Epitope Masking - Bergström, Joakim J. E.; Xu, Hui; Heyman, Birgitta (Frontiers in Immunology, 2017)
Specific IgG, passively administered together with particulate antigen, can completely prevent induction of antibody responses to this antigen. The ability of IgG to suppress antibody responses to sheep red blood cells (SRBC) is intact in mice lacking FcγRs, C1q, C3, or complement receptors 1 and 2, suggesting that Fc-dependent effector functions are not involved. Two of the most widely discussed explanations for the suppressive effect are increased clearance of IgG-antigen complexes and/or that IgG "hides" the antigen from recognition by specific B cells, so-called epitope masking. The majority of data on how IgG induces suppression was obtained through studies of the effects on IgM-secreting single spleen cells during the first week after immunization. Here, we show that IgG also suppresses antigen-specific extra-follicular antibody-secreting cells, germinal center B-cells, long-lived plasma cells, long-term IgG responses and induction of memory antibody responses. IgG anti-SRBC reduced the amount of SRBC in the spleens of wild-type but not of FcγR-deficient mice. However, no correlation between suppression and the amount of SRBC in the spleen was observed, suggesting that increased clearance does not explain IgG-mediated suppression. Instead we found compelling evidence for epitope masking because IgG anti-NP administered with NP-SRBC suppressed the IgG anti-NP but not the IgG anti-SRBC response. Vice versa, IgG anti-SRBC administered with NP-SRBC, suppressed only the IgG anti-SRBC response. In conclusion, passively transferred IgG suppressed all measured parameters of an antigen-specific antibody/B cell response and an important mechanism of action is likely to be epitope masking.